A brief review on extraction and characterization of nanocellulose from date palm biomass - Selvin P. Thomas (Journal of King Saud University: Engineering Sciences)
Abstract Developing value-added raw materials from agricultural waste is gaining momentum as it is useful on multiple grounds. Among the different materials developed nanocellulose has gained a lot of attention due to its exceptional properties which can be utilized to develop different devices. Nanocellulose from date palm waste materials has been studied by several research groups, especially in the Middle East and North Africa regions recently. This short review focuses on the extraction and characterization of nanocellulose derived from date palm, a readily available and renewable resource in this region. The review discusses various methods employed for the extraction and production of nanocellulose, including mechanical, chemical, and enzymatic processes. Key characterization techniques such as Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and transmission electron microscopy (TEM) are highlighted to elucidate the structural and morphological properties of nanocellulose. The findings underscore the potential of date palm-derived nanocellulose as a sustainable material for use in different areas. This review aims to provide a brief overview of the current advancements in the field of nanocellulose from date palm biomass. This review is essential because while nanocellulose offers tremendous potential as a renewable nanomaterial, the lack of standardized extraction and characterization methods leads to variability in product quality. By evaluating mechanical, chemical, and biological approaches across different date palm biomass sources, this work helps researchers optimize processes for high-performance nanocellulose while minimizing environmental impact. Additionally, it enables the reader to find out the latest reports in a nutshell which will help to bridge the gap between lab-scale studies and industrial adoption, offering clear pathways for commercialization.